CORRELATION BETWEEN GRANULOMETRY AND ORGANIC SOIL MATTERS WITH LIMITS OF ATTERBERG - Ribeiro, K. D.; Souza, L. K. (Revista Brasileira de Engenharia de Biossistemas, 2018)
The characterization of soils under mechanized agriculture is important for its correct management and prevention of compaction. Among the properties related to soil management, the granulometry and the organic matter content influence the consistency; and the consistency allows defining when a soil is friable, an ideal condition for mechanized agricultural practices. The objective of this work was to evaluate the correlation between soil consistency limits and grain size and organic matter content, aiming at the adequate management of soils under mechanized agriculture. Soil samples were collected at different depths, which were characterized by texture, organic matter content, plasticity limit, liquidity limit and plasticity index. The results showed that the studied area is characterized by a medium textured soil, moderately plastic and low organic matter concentration. It is recommended that mechanized agricultural practices be performed when soil moisture is below 29%. Soil granulometry had a significant influence on the soil consistency limits of the studied area and the soil organic matter concentration did not influence the values ​​of soil consistency limits.